Winners and losers in the privatization game - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The terms 'privatization' end 'liberalization' dominate politics these days. But in African agriculture these processes, which were introduced in response to economic crises, only serve to accentuate the division between the small peasant farmer and...